Digital culture as one of the pillars of digital transformation - Zegrire, Nacera; Redjem, Khaled (The International tax journal, 2025)
In light of the techno-cognitive transformations taking place worldwide across political, economic, social, and cultural fields—which have profoundly impacted individuals and societies—and with the shift toward knowledge-based societies, the concept of development has undeniably changed. Development no longer relies solely on material aspects but rather on cognitive and cultural dimensions. Achieving meaningful and sustainable development is only possible through effective engagement with information by implementing policies, strategies, and mechanisms for monitoring, organizing, retrieving, and optimally utilizing knowledge. This study aims to shed light on digital culture as one of the most critical factors for the success of digital transformation. It explores the concept of digital culture, its components, domains, and its current state in Algeria. A descriptive methodology was adopted due to its suitability for the study. The findings indicate that digital culture plays a vital role in ensuring the success of digital transformation and serves as a fundamental pillar for it.